COMPOSITIONS BASED ON AQUEOUS SOLUTIONS OF CHITOSAN AND GLUTAR ALDEHYDE FOR EMBOLIZATION OF BLOOD VESSELS - P. E. Ignatieva; E. S. Zhavoronok; O. A. Legonkova; S. A. Kedik (Тонкие химические технологии, 2019)
The article investigates the aqueous solutions of food chitosan and glutaraldehyde to determine the feasibility of their use as components of an embolizing composition. It was shown on the basis of experimental flow curves, viscosity and velocity curves that test solutions have low viscosity and exhibit Newtonian flow behavior. The activation energy of viscous flow of the fluids was estimated in the temperature range of 25-37 °C within the Arrhenius - Frenkel - Eyring equation. It varies within a narrow range: 17-24 kJ/mol. When mixing the aqueous solutions of food chitosan and glutaraldehyde, chemical interaction of the solutes occurs. It is accompanied by an increase in viscosity and formation of a covalently crosslinked gel. Using a simple exponential equation the effective rate constant of the chemical process was calculated. It varies in a wide range: 1.9-82.7∙103 1/s. These values can be used when selecting an optimal region of food chitosan-glutaraldehyde ratios and concentrations of their aqueous solutions to generate embolizing agents. The conditions at which gel formation takes place over forty seconds were determined. Differential scanning calorimetry indicated a negligible thermal effect of food chitosan reaction with glutaraldehyde in the aqueous medium, which ensures no thermal burn during the formation of an embolus in the blood vessel in situ. As a result of the work elastic solid gels suitable for use as embolizing agents were obtained.